Holding the executive accountable: parliament as the beacon of hope to the people - Zitha, H. E.; .Sebola, M. P. (My University, 2016)
This article investigates compliance to procurement processes and its effect on service delivery in the public sector. Public procurement non-compliance has triggered a lot of debate in recent years. Due to colossal amount of money involved in government procurement and the fact that such money comes from the public, there is a need for accountability and transparency. In order for government to realise the provisions of section 195 of the Constitution of the Republic of South Africa, 1996 government departments are required to comply with the rules, regulations and prescripts governing procurement of goods and services. For instance, in 2011, five Provincial Departments in Limpopo Province were put under administration in terms of Section 100 (1) (b) of the Constitution of the Republic of South Africa (1996). Procurement was mentioned as one of the weaknesses that contributed to the impasse. According to Smart Procurement (2011), despite the reform processes in public procurement and employment as strategic tool, there are predicaments in South African public procurement practices. This article is conceptual in nature and it explores the deviant human behaviour in relation to procurement compliance. There are various theories that did an exploration on the deviant behaviour of human beings which is the centre focus of the study. However the article will focus on social bond theory given the relevancy of their exposition to the study. The articleconcludes that only compliance to procurement guidelines will ensure service delivery, in South Africa public services.
Published in: Journal of Public Administration and Development Initiatives, volume 1. issue 1, 2016
Keywords: Compliance; Procurement process; Service delivery; Public sector; Government purchasing -- South Africa